2016
DOI: 10.1111/jan.13212
|View full text |Cite
|
Sign up to set email alerts
|

‘Mental health day’ sickness absence amongst nurses and midwives: workplace, workforce, psychosocial and health characteristics

Abstract: Aim To examine the workforce, workplace, psychosocial and health characteristics of nurses and midwives in relation to their reported use of sickness absence described as ‘mental health days’. Background The occupational stress associated with the nursing profession is increasingly recognized and nurse/midwifery absenteeism is a significant global problem. Taking a ‘mental health day’ as sickness absence is a common phenomenon in Australian health care. No previous studies have empirically explored the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 34 publications
2
35
1
5
Order By: Relevance
“…El presenteísmo está relacionado con la seguridad del paciente; con mayor caída de pacientes y errores de medicación que generan costos estimados en aproximadamente dos mil millones por año a los Estados Unidos (5) . Además de eso, la literatura identifica el ausenteísmo (ausencias al trabajo) como un problema global (6,7) y reconoce que el absentismo por enfermedad promueve la sobrecarga de trabajo, afecta el funcionamiento del lugar de trabajo, el equipo y los usuarios, comprometiendo la calidad y seguridad de la asistencia de enfermería y la eficiencia de los servicios (6,8,9) . En este momento en que es necesario explorar todas las posibilidades para mejorar la calidad y disminuir costos relacionados a los cuidados (5) la salud de los profesionales de enfermería debe recibir cuidado adecuado.…”
Section: Enfermería Globalunclassified
See 1 more Smart Citation
“…El presenteísmo está relacionado con la seguridad del paciente; con mayor caída de pacientes y errores de medicación que generan costos estimados en aproximadamente dos mil millones por año a los Estados Unidos (5) . Además de eso, la literatura identifica el ausenteísmo (ausencias al trabajo) como un problema global (6,7) y reconoce que el absentismo por enfermedad promueve la sobrecarga de trabajo, afecta el funcionamiento del lugar de trabajo, el equipo y los usuarios, comprometiendo la calidad y seguridad de la asistencia de enfermería y la eficiencia de los servicios (6,8,9) . En este momento en que es necesario explorar todas las posibilidades para mejorar la calidad y disminuir costos relacionados a los cuidados (5) la salud de los profesionales de enfermería debe recibir cuidado adecuado.…”
Section: Enfermería Globalunclassified
“…riesgo para resultados adversos a la salud (7) . Los resultados relacionados al estrés y salud tienen como importantes predictores las características relacionadas al trabajo y el ambiente en que los enfermeros desarrollan sus actividades laborales (17) .…”
Section: Nº 51 Julio 2018unclassified
“…They found that the factors related to mental health that contributed to absenteeism among nurses and midwives are: starting a career, multiple work, demanding work, abuse at work, smoking, symptoms of mental disorders, desire for cancellation, use of psychotropic medicines and insomnia. The authors state that on the basis of findings on the connection of mental health with absenteeism in health care system, the specific characteristics of employees could be used as indicators for the early identification of individuals who are at risk of absenteeism (Lamont et al, 2016).…”
mentioning
confidence: 99%
“…Therefore, identifying and understanding the factors contributing to absenteeism is a particularly challenging for society (Waage and Bjorvatn, 2016). In addition to other factors, the causes of absenteeism are often attributed to mental disorders (Lamont et al, 2016;Perry et al, 2015). When absenteeism arises from mental health problems, employees are usually absent for a longer period of time, and consequently this Absenteeism due to mental problems among employees in nursing Brigita Jeretina 1 , Katja Krt 2 , Andrej Starc can lead to permanent incapacity for work (Anema et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation